RESPON FISIOLOGIS AYAM PETELUR FASE GROWER PADA KEPADATAN KANDANG YANG BERBEDA - Rosaliya Imelda; Sri Suharyati; Veronica Wanniatie (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The experiment was determine to physiological responses of laying hens grower phases atdifferent stocking density and determine the effect of stocking density best on the physiologicalresponses of laying hens grower phases. Research carried out for 3 weeks from 2 April to 23 April2014, in Varia Agung Jaya Farm, Varia Agung Village, District of seputih Mataram, LampungTengah Regency. Chicken laying hens used were 8-10 weeks of age grower phases as much as 210.This study used a Completely Randomized Design (CRD), consisting of four treatments, replicatedfive times, namely P1: 6 m-2 tail cage density, P2: 9 m-2 tail cage density, P3: 12 m-2 tail cage density,P4: 15 m-2 tail cage density. The resulting data were analyzed by analysis of variance at the 5%significance level.The results show that stocking density 6, 9, 12 and 15 m-2 individuals per had no significanteffect (P<0.05) on physiological responses (respiratory rate, rectal temperature and temperatureshank) chicken laying grower phases.